Assessing the water quality of the Seine land-to-sea continuum for three agro-food system scenarios - Romero, Estela; Garnier, Josette; Billen, Gilles; Ramarson, Antsiva; Riou, Philippe; Le Gendre, Romain (Frontiers in Marine Science, 2022)
Three scenarios for the future of the French agro-food system were specified for the territory draining into the Seine Bight, comprising Paris megacity and the Seine watershed. The first scenario assumes the pursuit of the current trend of opening and specialization of agriculture, as well as of concentration of population within the Paris agglomeration. The second scenario assesses the generalization of agro-ecological practices and a healthier human diet. A third, hybrid, scenario was elaborated, assuming that agro-ecological practices were implemented in some protected areas (namely Regional Natural Parks and drinking water protection areas, making up about one-third of the total watershed area), while the rest of the territory will follow the trends of the first scenario. We use a unique modelling chain (GRAFS-Riverstrahler-ECOMARS3D) that couples the biogeochemical functioning of the river basin, the estuary and the adjacent bay. It allows exploring the implications of changes in terrestrial activities throughout the aquatic continuum in a consistent way and assessing to what extent changes in population, agricultural practices, food consumption, and sanitation may sustain the current trend of recovery in the Seine River or increase stress on the system. Results show that only the full agro-ecological scenario would be able to restore good water quality everywhere in the river network, as well as decrease significantly the risks of toxic algal blooms in the coastal zone. Intermediate situations, such as the protection of specific areas, however attractive as a solution, are not enough to offset the impacts of intensive human activities unless the protected areas dedicated to compensating for damage are sufficiently large.